Retracted: Using Big Data-Based Neural Network Parallel Optimization Algorithm in Sports Fatigue Warning - Intelligence and Neuroscience, Computational (Computational intelligence and neuroscience, 2023)
[This retracts the article DOI: 10.1155/2021/2747940.].